PERAN ORANG TUA MENGGUNAKAN METODE TARGHIB WAT TARHIB DALAM MENINGKATKAN KEDISIPLINAN BERIBADAH ANAK - Eka Wahyu Hidayati (Institut Keislaman Abdullah Faqih Gresik, 2020)
The TarghÄ«b Wat TarhÄ«b method which is applied to influence the child's soul to be able to do good deeds and stay away from bad deeds. This method also teaches about how to educate by conveying / using persuasion / seduction and threats / punishment in accordance with Islamic teachings. This research method uses a quantitative approach with questionnaire and interview data sources.Â This research results in the role of parents with the TarghÄ«b Wat TarhÄ«b method (suggestion / threat) which is very good discipline for children worship. This is evidenced by the value of Y = 15.960 + 0.760 X, which means that every 1% addition of the level of parental role with the TarghÄ«b Wat TarhÄ«b Method, the discipline of worshiping teenagers will increase by 0.760. This value also has a significant effect on the results of the t test, which shows the t count of 9.847> 2.045 (t table) with a Sig value of 0.00 < a probability value of 0.05, which means that Ho is rejected and Ha is accepted. Therefore,